2018
DOI: 10.3390/ijms19082275
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Mechanism of Gloverin2 from Silkworm, Bombyx mori

Abstract: Gloverin is one of the glycine-rich antimicrobial peptide exclusively found in Lepidoptera insects. It is generally activated through the innate immune system in insects. In this study, recombinant Gloverin2 from Bombyx mori (BmGlv2) was synthesized using a prokaryotic expression system. Circular dichroism spectroscopy showed that the recombinant BmGlv2 has random coil structure, which is relatively stable at the temperatures ranging from 15 to 82.5 °C. Antimicrobial activity analysis revealed that BmGlv2 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The lower concentrations (0.075 and 0.15 µg/µL) did not induce relevant effects on the culture; only by incubation with 0.25 µg/µL did the growth drastically decrease to 12.5%. These data agree with the results by Wang et al [40], who have shown that gloverin exerts antibacterial effects mainly on Gram-negative bacteria and fungi, with varying efficacy depending on the insect species considered. Moreover, since different microorganisms induce different immune signaling pathways, gloverins are generally considered to be induced through Toll and Imd pathways during immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…The lower concentrations (0.075 and 0.15 µg/µL) did not induce relevant effects on the culture; only by incubation with 0.25 µg/µL did the growth drastically decrease to 12.5%. These data agree with the results by Wang et al [40], who have shown that gloverin exerts antibacterial effects mainly on Gram-negative bacteria and fungi, with varying efficacy depending on the insect species considered. Moreover, since different microorganisms induce different immune signaling pathways, gloverins are generally considered to be induced through Toll and Imd pathways during immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…The main reason may be that lipid-peptide interaction in live bacteria is a dynamic process that causes transient disruption of the cell membrane without destroying its structural integrity [27]. Some studies have reported that AMPs mainly acted on the membrane and led to cell death such as T9W, tachyplesin I, cathelicidin, and bovine lactoferricin derivatives [28][29][30][31][32]. Some results indicated that AMPs had different locations for killing different species of microbes such as Bac7 and SpHyastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The immunofluorescence localization in P. pastoris was performed as previously described (Wang et al ., 2018). Briefly, P. pastoris strains induced with methanol for 4 days were incubated with normal goat serum (final concentration of 5%, Solarbio, Beijing, China) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%